Plant Polyphenols as Chemopreventive Agents for Lung Cancer - Amararathna, Madumani (Int J Mol Sci, 2016)
Lung cancer may be prevented by a diet rich in fruits and vegetables as they are enriched with dietary antioxidant polyphenols, such as flavonoids, proanthocyanidins, lignans, stilbenes, and phenolic acids. Dietary polyphenols exert a wide range of beneficial biological functions beyond their antioxidative properties and are involved in regulation of cell survival pathways leading to anticarcinogenic and antimutagenic functions. There are sufficient evidence from in vitro, in vivo, and epidemiological studies to suggest that the dietary intervention of polyphenols in cancer prevention, including the chemopreventive ability of dietary polyphenols, act against lung carcinogens. Cohort and epidemiological studies in selected risk populations have evaluated clinical effects of polyphenols. Polyphenols have demonstrated three major actions: antioxidative activity, regulation of phase I and II enzymes, and regulation of cell survival pathways against lung carcinogenesis. They have also shown an inverse association of lung cancer occurrences among high risk populations who consumed considerable amounts of fruits and vegetables in their daily diet. In in vitro cell culture experimental models, polyphenols bind with electrophilic metabolites from carcinogens, inactivate cellular oxygen radicals, prevent membrane lipid peroxidation and DNA oxidative damage, and adduct formation. Further, polyphenols enhance the detoxifying enzymes such as the phase II enzymes, glutathione transferases and glucuronosyl transferases.